Oxygen isotope trajectories of crystallizing melts: Insights from modeling and the plutonic record. (15th June 2017) - Bucholz, Claire E.; Jagoutz, Oliver; VanTongeren, Jill A.; Setera, Jacob; Wang, Zhengrong
Abstract: Elevated oxygen isotope values in igneous rocks are often used to fingerprint supracrustal alteration or assimilation of material that once resided near the surface of the earth. The δ 18 O value of a melt, however, can also increase through closed-system fractional crystallization. In order to quantify the change in melt δ 18 O due to crystallization, we develop a detailed closed-system fractional crystallization mass balance model and apply it to six experimentally- and naturally-determined liquid lines of descent (LLDs), which cover nearly complete crystallization intervals (melt fractions of 1 to <0.1). The studied LLDs vary from anhydrous tholeiitic basalts to hydrous high-K and calc-alkaline basalts and are characterized by distinct melt temperature-SiO2 trajectories, as well as, crystallizing phase relationships. Our model results demonstrate that melt fraction-temperature-SiO2 relationships of crystallizing melts, which are strongly a function of magmatic water content, will control the specific δ 18 O path of a crystallizing melt. Hydrous melts, typical of subduction zones, undergo larger increases in δ 18 O during early stages of crystallization due to their lower magmatic temperatures, greater initial increases in SiO2 content, and high temperature stability of low δ 18 O phases, such as oxides, amphibole, and anorthitic plagioclase (versus albite). Conversely, relatively dry, tholeiitic melts only experience significant increases in δ 18 O at degrees of crystallization greater than 80%. Total calculated increases in melt δ 18 O of 1.0–1.5‰ can be attributed to crystallization from ∼50 to 70 wt.% SiO2 for modeled closed-system crystallizing melt compositions. As an example application, we compare our closed system model results to oxygen isotope mineral data from two natural plutonic sequences, a relatively dry, tholeiitic sequence from the Upper and Upper Main Zones (UUMZ) of the Bushveld Complex (South Africa) and a high-K, hydrous sequence from the arc-related Dariv Igneous Complex (Mongolia). These two sequences were chosen as their major and trace element compositions appear to have been predominantly controlled by closed-system fractional crystallization and their LLDs have been modeled in detail. We calculated equilibrium melt δ 18 O values using the measured mineral δ 18 O values and calculated mineral-melt fractionation factors. Increases of 2–3‰ and 1–1.5‰ in the equilibrium melts are observed for the Dariv Igneous Complex and the UUMZ of the Bushveld Complex, respectively. Closed-system fractional crystallization model results reproduce the 1‰ increase observed in the equilibrium melt δ 18 O for the Bushveld UUMZ, whereas for the Dariv Igneous Complex assimilation of high δ 18 O material is necessary to account for the increase in melt δ 18 O values. Assimilation of evolved supracrustal material is also confirmed with Sr and Nd isotope analyses of clinopyroxene from the sequence. Beginning with a range of mantle-derived basalt δ 18 O values of 5.7‰ ("pristine" mantle) to ∼7.0‰ (heavily subduction-influenced mantle), our model results demonstrated that high-silica melts (i.e. granites) with δ 18 O of up to 8.5‰ can be produced through fractional crystallization alone. Lastly, we model the zircon-melt δ 18 O fractionations of different LLDs, emphasizing their dependence on the specific SiO2 - T relationships of a given crystallizing melt. Wet, relatively cool granitic melts will have larger zircon-melt fractionations, potentially by ∼1.5‰, compared to hot, dry granites. Therefore, it is critical to constrain zircon-melt fractionations specific to a system of interest when using zircon δ 18 O values to calculate melt δ 18 O.